Flow Velocity Gradient of Refined Hydrocarbon and Viscous Fluid in A Single Stage Symmetrical Bifurcated Channel - Egbo A. Chijioke; Ahmed M. Hassan; Opuene D. Ogisobo; Nama K. Faket; Onoja I. Valens; Oluomachukwu P. Onwe (PT FORMOSA CENDEKIA GLOBAL, 2022)
A single stage bifurcated system in its wide spectrum of applications in the petroleum and gas processing industry, chemical industry and civil engineering industry, in the distribution and recovery of processed and unprocessed fluid and materials. Considered in this experimental investigation of the impact of a single stage symmetrical bifurcated system on the flow of viscous fluid and refined hydrocarbon to truly establish a relationship between specific dimensions of symmetrical bifurcated flow channels and the physical properties of various classes of fluid samples. Peanut oil and diesel were selected to respectively represent viscous fluid and refined hydrocarbon, as they are allowed to flow through some selected angles of a single stage symmetrical bifurcated channel until designated volumes of each of the fluid samples are recovered into a recovery beaker. Profile of results presented from the experimental study reveals a trend with a sharp negative velocity gradient for small flow time corresponding to smaller recovery volume and a much lower velocity gradient for relatively higher flow time for higher recovery volume for less viscous and dense diesel oil representing refined hydrocarbon and a more viscous and dense peanut oil represented by the trend with a lower negative velocity gradient. The implication of the results obtained is that bifurcated systems offer flow stability in a continuous flow situation, and also observed from the results is the confirmation of the existence of velocity gradient between opposite wall of the branched channels, which further reveals where the flow state will eventually begin to graduate into turbulence. The study can be extended by investigating the impact of two-stage or multiple level bifurcated network system on flow structure and stability, and how the pressure based on the level of fluid in the reservoir is related to the flow velocity and stability.